2008
DOI: 10.4049/jimmunol.181.9.6654
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived IFN-Producing Killer Dendritic Cells Account for the Tumoricidal Activity of Unpulsed Dendritic Cells

Abstract: The CD11cintB220+NK1.1+CD49+ subset of cells has recently been described as IFN-producing killer dendritic cells (IKDC), which share phenotypic and functional properties of dendritic cells and NK cells. Herein we show that bone marrow-derived murine dendritic cell preparations contain abundant CD11cintB220+NK1.1+CD49+ cells, the removal of which results in loss of tumoricidal activity of unpulsed dendritic cells in vivo. Moreover, following s.c. injection, as few as 5 × 103 highly pure bone marrow-derived IKDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…34 Of interest, 5 mouse cancer quantitative trait loci (http://tumor.informatics.jax.org) and Ն 5 of the quantitative trait loci linked to the most frequent human cancers are syntenic to this same distal region of mouse chromosome 7. [47][48][49] Because pre-mNK cells exhibit a prominent antitumoral potential, 14,20,21 it is tempting to speculate that genes defining the proportion of pre-mNK cells also contribute toward defining cancer susceptibility. Indeed, on a per cell basis, the in vivo antitumoral activity of pre-mNK cells is more efficient than mNK cells, 14,16,[20][21][22] probably because of the fact that, as an immediate precursor population, pre-mNK cells can generate a vast number of mNK cells.…”
Section: Ikdc Are Precursors To Mature Nk Cells 4355mentioning
confidence: 99%
See 1 more Smart Citation
“…34 Of interest, 5 mouse cancer quantitative trait loci (http://tumor.informatics.jax.org) and Ն 5 of the quantitative trait loci linked to the most frequent human cancers are syntenic to this same distal region of mouse chromosome 7. [47][48][49] Because pre-mNK cells exhibit a prominent antitumoral potential, 14,20,21 it is tempting to speculate that genes defining the proportion of pre-mNK cells also contribute toward defining cancer susceptibility. Indeed, on a per cell basis, the in vivo antitumoral activity of pre-mNK cells is more efficient than mNK cells, 14,16,[20][21][22] probably because of the fact that, as an immediate precursor population, pre-mNK cells can generate a vast number of mNK cells.…”
Section: Ikdc Are Precursors To Mature Nk Cells 4355mentioning
confidence: 99%
“…Consequently, cells carrying the IKDC phenotype are now more commonly referred to as activated B220 ϩ NK cells. 18 Nevertheless, the exact lineage relation of B220 ϩ NK cells, which arguably present with the most efficient antitumoral potential relative to other mNK-cell subsets, 14,16,[20][21][22] has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous data showed that IKDCs were present in high amounts in bone marrow DC preparations and that there was an absolute requirement of IKDCs within therapeutic DC preparations to induce a tumor response to unpulsed DCs. We also showed that the tumoricidal activity of BM-IKDCs is lost in hosts lacking functional T cells and NK cells, implying that induction of secondary immune responses is vital for BM-IKDC tumoricidal effects (11).…”
Section: Discussionmentioning
confidence: 80%
“…In adoptive transfer experiments, purified IKDCs from bone marrow (BM-IKDC) were effective at eliminating tumor cells implanted at distant s.c. sites, using a mechanism that is dependent on effector cells of the host immune system (11). We here show that highly purified IKDCs are capable of cross-presenting tumor antigens in vitro and that in vivo cross-presentation occurs during the process of tumor rejection by IKDCs.…”
Section: Cd49bmentioning
confidence: 83%
“…[1][2][3][4] In this issue of Blood, Guimont-Desrochers et al redefine B220 ϩ NK cells as a novel intermediate in NK-cell differentiation preceding the acquisition of CD27. 5 …”
Section: Ikdcs or B220 ؉ Nk Cells Are Pre-mnk Cells -----------------mentioning
confidence: 99%